Two-Sided RRT* Planner Considering Inter-Node Maximum Length Connection on Adversarial Workspaces for AGV - Pamosoaji, Anugrah K (Jurnal Buana Informatika, 2025)
This paper presents a two-sided Rapidly-Explored Random Tree (RRT*) which is a variant of RRT* path planning algorithm that utilizes a start and a target node as the bases for generating paths. The advantage of this method is in the capability to make a connection between start and target nodes under adversarial workspace. In this type of workspaces, the main problem in RRT* is the success rate of constructing a complete and optimized route and reducing path-generation processing time. The proposed algorithm is purposed to increase the route generation success rate and reduce the processing time. The technique consists of two-fold: the application of maximum length of inter-node path and two-sided node generation, i.e., from the start and target nodes. Simulation results conclude that the application of large maximum length of inter-node path can increase the success rate of complete route construction.